Wireless Sensor for Meat Freshness Assessment Based on Radio Frequency Communication - Andre, Rafaela S.; Schneider, Rodrigo; DeLima, Guilherme R. [UNESP]; Fugikawa-Santos, Lucas [UNESP]; Correa, Daniel S. (American Chemical Society (ACS), 2024)
Wireless communication technologies, particularly radio frequency (RF), have been widely explored for wearable electronics with secure and user-friendly information transmission. By exploiting the operational principle of chemically actuated resonant devices (CARDs) and the electrical response observed in chemiresistive materials, we propose a simple and hands-on alternative to design and manufacture RF tags that function as CARDs for wireless sensing of meat freshness. Specifically, the RF antennas were meticulously designed and fabricated by lithography onto a flexible substrate with conductive tape, and the RF signal was characterized in terms of amplitude and peak resonant frequency. Subsequently, a single-walled carbon nanotube (SWCNT)/MoS2/In2O3 chemiresistive composite was incorporated into the RF tag to convey it as CARDs. The RF signal was then utilized to establish a correlation between the sensor’s electrical response and the RF attenuation signal (reflection coefficient) in the presence of volatile amines and seafood (shrimp) samples. The freshness of the seafood samples was systematically assessed throughout the storage time by utilizing the CARDs, thereby underscoring their effective potential for monitoring food quality. Specifically, the developed wireless tags provide cumulative amine exposure data within the food package, demonstrating a gradual decrease in radio frequency signals. This study illustrates the versatility of RF tags integrated with chemiresistors as a promising pathway toward scalable, affordable, and portable wireless chemical sensors.
Keywords: ammonia; meat freshness; radio frequency; sensors; wireless communication